Examining Procedural Legal Challenges of Ethiopian Electoral Law Frameworks for Realizing Electoral Justice in Court Litigation - Mengesha, Abenezer Nahome (Bahir Dar University Journal of Law, 2024)
An effective electoral dispute resolution system is crucial to any democratic process. Such a system guarantees that all eligible voters can participate, that elections are conducted fairly and transparently, and that results truly reflect the voters’ will.Furthermore, it fosters trust in both the electoral process and the broader democratic system by providing a clear mechanism for resolving disputes.This research examines how Ethiopian electoral law and the election dispute resolution system align with international standards and best practices. The study aims to identify the nature and type of the current system and to assess the challenges associated with achieving electoral justice through court litigation. The researcher employed a doctrinal research method to explore procedural legal challenges and analyzed selected court decisions to illustrate their practical effects. The findings indicate that significant procedural legal challenges exist within the current legal framework for ensuring electoral justice through court litigation. These challenges include: the absence of a specific procedural law addressing election disputes, unclear provisions in the election proclamation regarding the finality of appellate court decisions, and a lack of clarity on jurisdiction for disputes, particularly those related to candidate registration, voter registration, and the voting process in specific jurisdictions such as Addis Ababa and Dire Dawa. Based on these findings, the study proposes recommendations to enhance the effectiveness of the electoral dispute resolution system in Ethiopia.